How Biodiversity-Friendly Is Regenerative Grazing? - Morris, Craig D. (Frontiers in Ecology and Evolution, 2021)
Regenerative grazing management (ReGM) seeks to mimic natural grazing dynamics to restore degraded soils and the ecological processes underpinning sustainable livestock production while enhancing biodiversity. Regenerative grazing, including holistic planned grazing and related methods, is an adaptive, rotational stocking approach in which dense livestock herds are rotated rapidly through multiple paddocks in short bouts of grazing to defoliate plants evenly and infrequently, interspersed with long recovery periods to boost regrowth. The concentrated ‘hoof action’ of herds in ReGM is regarded vital for regenerating soils and ecosystem services. Evidence (from 58 studies) that ReGM benefits biodiversity is reviewed. Soils enriched by ReGM have increased microbial bioactivity, higher fungal:bacteria biomass, greater functional diversity, and richer microarthropods and macrofauna communities. Vegetation responds inconsistently, with increased, neutral, or decreased total plant diversity, richness of forage grasses and invasive species under ReGM: grasses tend to be favoured but shrubs and forbs can be depleted by the mechanical action of hooves. Trampling also reduces numerous arthropods by altering vegetation structure but creates favourable habitat and food for a few taxa, such as dung beetles. Similarly, grazing-induced structural changes benefit some birds (for foraging, nest sites) while heavy stocking during winter and droughts reduce food for seedeaters and songbirds. With herding and no fences, wildlife (herbivores and predators) thrives on nutritious regrowth while having access to large undisturbed areas. It is concluded that ReGM does not universally promote biodiversity but can be adapted to provide greater landscape habitat heterogeneity suitable to a wider range of biota.